2010
DOI: 10.2146/ajhp100196
|View full text |Cite
|
Sign up to set email alerts
|

Mental health stability in veterans with posttraumatic stress disorder receiving varenicline

Abstract: Varenicline appeared to have destabilizing effects on MH in veterans with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…7 At the Veterans Affairs Medical Center (VAMC), varencline, a second-line medication with a reported 25% abstinence rate, is considered only after bupropion or nicotine replacement therapy or a combination of the two have failed, and then only after appropriate psychiatric and cardiovascular screening. [7][8][9][10][11][12] Alternatives to pharmacological therapies such as acupuncture, acupressure, and electrical stimulation have received minimal attention in the re-search but are used widely, and proponents of their use believe them to be effective and safe interventions for smoking. 13 However, a recent Cochrane review found little evidence from randomized controlled trials that any of these therapies work better than placebo.…”
mentioning
confidence: 99%
“…7 At the Veterans Affairs Medical Center (VAMC), varencline, a second-line medication with a reported 25% abstinence rate, is considered only after bupropion or nicotine replacement therapy or a combination of the two have failed, and then only after appropriate psychiatric and cardiovascular screening. [7][8][9][10][11][12] Alternatives to pharmacological therapies such as acupuncture, acupressure, and electrical stimulation have received minimal attention in the re-search but are used widely, and proponents of their use believe them to be effective and safe interventions for smoking. 13 However, a recent Cochrane review found little evidence from randomized controlled trials that any of these therapies work better than placebo.…”
mentioning
confidence: 99%
“…An open label trial of 112 smokers with stable schizophrenia also found no exacerbation of psychosis (Pachas et al, 2012). In a retrospective analysis of 78 veterans with posttraumatic stress disorder, two patients were found to have depressive episodes attributable to varenicline treatment, and four other patients had suicidal ideation or mental health-related hospitalizations not attributed to varenicline (Campbell, 2010). In another retrospective cohort of 50 veterans prescribed varenicline, four patients with underlying psychiatric illness discontinued therapy due to behavioral changes (Purvis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular importance in a veteran population due to the increased prevalence of both nicotine dependence and comorbid psychiatric illness. Retrospective data indicate that the mental health of patients with PTSD may be destabilized while receiving varenicline (Campbell & Anderson, 2010). Perhaps most troubling are the substantially more reports of suicidal behavior in patients receiving varenicline as compared to other smoking cessation therapies (Moore, Furberg, Glenmullen, Maltsberger, & Singh, 2011).…”
Section: Discussionmentioning
confidence: 99%